C++20 Fundamentals - Deitel, Paul (Pearson, 2020)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing. C++20 Fundamentals LiveLessons with Paul Deitel is a code-oriented presentation of C++, one of the world'Äôs most versatile and powerful programming languages. C++ remains hugely popular for the development of systems software, embedded systems, operating systems, real-time systems, communications systems and other high performance computer applications. C++20 Fundamentals LiveLessons is comprehensive and covers all major versions of C++, including: C++11, C++17, and C++20.